Characterization and Inhibition of a Nickel-Alpha-Hydroxyoxime (LIX 63) Salt Precipitate Formed under Proposed Commercial Operating Conditions - Barnard, K.; Shiers, D.; McIldowie, Matthew; Skelton, B.; Ogden, Mark; McCoy, T. (American Chemical Society, 2014)
As a prospective commercial solvent extraction (SX) process, laboratory-scale continuous tests were recently undertaken to assess the use of a solution of LIX 63 hydroxyoxime (“hydroxyoxime”) and Versatic 10 to kinetically separate cobalt from a nickel-rich sulfate solution while simultaneously rejecting manganese and magnesium. A material quantity of blue precipitate observed in the strip stage cells during decommissioning has been identified as the sulfate salt of the nickel-trishydroxyoxime complex. As precipitation during SX is undesirable, the effect of various operating parameters on precipitate formation has been investigated. Minimizing aqueous nickel and/or sulfuric acid concentration and/or increasing organic polarity can overcome this problem. Where it forms, hydroxyoxime and nickel can be recovered from the precipitate by redissolution under suitable (e.g., low acid) operating conditions. The nitrate salt counterpart of this sulfate precipitate has beencrystallographically characterized using a short chained (C8) analogue of LIX 63 hydroxyoxime, revealing the coordination of three neutral hydroxyoxime ligands around nickel, forming a monomeric coordination complex cation counterbalanced by nitrate anions.